Words, Deeds, Bodies: J. L. Austin, Wittgenstein, Merleau-Ponty, and Michael Polanyi - Gill, Jerry H,, (Value Inquiry Book Series ;, 2019)
Words, Deeds, Bodies by Jerry H. Gill concentrates on the interrelationships between speech, accomplishing tasks, and human embodiment. Ludwig Wittgenstein, J. L. Austin, Maurice Merleau-Ponty, and Michael Polanyi have all highlighted these relationships. This book examines the, as yet, unexplored connections between these authors' philosophies of language. It focuses on the relationships between their respective key ideas: Wittgenstein's notion of "language game," Austin's concept of "performative utterances," Merleau-Ponty's idea of "slackening the threads," and Polanyi's understanding of "tacit knowing," noting the similarities and differences between and amongst them.